Nuclear Translocation of Papillomavirus Minor Capsid Protein L2 Requires Hsc70 - Florin, Luise (American Society for Microbiology, 2004)
Minor capsid protein L2 of papillomaviruses plays an essential role in virus assembly by recruiting viral components to PML bodies, the proposed sites of virus morphogenesis. We demonstrate here that the function of L2 in virus assembly requires the chaperone Hsc70. Hsc70 was found dispersed in naturally infected keratinocytes and cultured cells. A dramatic relocation of Hsc70 from the cytoplasm to PML bodies was induced in these cells by L2 expression. Hsc70-L2 complex formation was confirmed by coimmunoprecipitation. The complex was modulated by the cochaperones Hip and Bag-1, which stabilize and destabilize Hsc70-substrate complexes, respectively. Cytoplasmic depletion of Hsc70 caused retention of wild-type and N-terminally truncated L2, but not of C-terminally truncated L2, in the cytoplasm. This retention was partially reversed by overexpression of Hsc70 fused to green fluorescent protein but not by ATPase-negative Hsc70. Hsc70 associated with L1-L2 virus-like particles (VLPs) but not with VLPs composed either of L1 alone or of L1 and C-terminally truncated L2. Moreover, displacement of Hsc70 from L1-L2 VLPs by encapsidation of DNA, generating pseudovirions, was found. These data indicate that Hsc70 transiently associates with viral capsids during the integration of L2, possibly via the L2 C terminus. Completion of virus assembly results in displacement of Hsc70 from virions.